Clinical and HLA genotype analysis of immune checkpoint inhibitor-associated diabetes mellitus: a single-center case series from China - Liu, Yi-chen; Liu, Hong; Zhao, Shao-li; Chen, Ke; Jin, Ping (Frontiers in Immunology, 2023)
Objective: To investigate the clinical characteristics and HLA genotypes of patients with immune checkpoint inhibitor-associated diabetes mellitus (ICI-DM) in China. Methods: We enrolled 23 patients with ICI-DM and 51 patients with type 1 diabetes (T1D). Clinical characteristics of the patients were collected. HLA-DRB1, HLA-DQA1, and HLA-DQB1 genotyping was conducted via next-generation sequencing. Results: The ICI-DM patients had a male predominance (70.6%), a mean body mass index (BMI) of 21.2±3.5 kg/m2, and a mean onset of ICI-DM in 5 (IQR, 3-9) cycles after ICI therapy. Most (78.3%) ICI-DM patients were treated with anti-PD-1, 78.3% presented with diabetic ketoacidosis, and all had low C-peptide levels and received multiple insulin injections. Compared to T1D patients, ICI-DM patients were significantly older (57.2±12.4 vs 34.1±15.7 years) and had higher blood glucose but lower HbA1c levels (P<0.05). Only two (8.7%) ICI-DM patients were positive for islet autoantibodies, which was lower than that in T1D patients (66.7%, P<0.001). A total of 59.1% (13/22) of ICI-DM patients were heterozygous for an HLA T1D risk haplotype, and DRB1*0901-DQA1*03-DQB1*0303 (DR9) and DRB1*0405-DQA1*03-DQB1*0401 were the major susceptible haplotypes. Compared to T1D, the susceptible DR3-DQA1*0501-DQB1*0201 (DR3) and DR9 haplotypes were less frequent (17.7% vs 2.3%; P=0.011 and 34.4% vs 15.9%; P=0.025), whereas the protective haplotypes (DRB1*1101-DQA1*05-DQB1*0301 and DRB1*1202-DQA1*0601-DQB1*0301) were more frequent in ICI-DM patients (2.1% vs 13.6%; P=0.006 and 4.2% vs 15.9%; P=0.017). None of the ICI-DM patients had T1D-associated high-risk genotypes DR3/DR3, DR3/DR9, and DR9/DR9. Among the 23 ICI-DM patients, 7 (30.4%) presented with ICI-associated fulminant type 1 diabetes (IFD), and 16 (69.6%) presented with ICI-associated type 1 diabetes (IT1D). Compared to IT1D patients, IFD patients exhibited marked hyperglycemia and low C-peptide and HbA1c levels (P<0.05). Up to 66.7% (4/6) of IFD patients were heterozygous for reported fulminant type 1 diabetes susceptibility HLA haplotypes (DRB1*0405-DQB1*0401 or DRB1*0901-DQB1*0303). Conclusion: ICI-DM shares similar clinical features with T1D, such as acute onset, poor islet function and insulin dependence. However, the lack of islet autoantibodies, the low frequencies of T1D susceptibility and high frequencies of protective HLA haplotypes indicate that ICI-DM represents a new model distinct from classical T1D.